2000
DOI: 10.1081/jdi-100100869
|View full text |Cite
|
Sign up to set email alerts
|

Cephotaxime-Associated Allergic Interstitial Nephritis and Mpo-Anca Positive Vasculitis

Abstract: We report a case of reversible acute renal failure after cefotaxime treatment in a patient affected by non-Hodgkin lymphoma. Renal biopsy showed necrotizing vasculitis associated with eosinophil-rich interstitial inflammatory infiltrates and patchy infiltrates of CD20+ lymphoid cells. High serum p-ANCA titers were also detected. Drug withdrawal was closely related with recovery of renal function and disappearance of ANCA. Acute renal failure therefore represented a consequence of ANCA-mediated renal vasculitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Both isoniazid and rifampin have been implicated as causes of vasculitis in case reports (60,61), but the association between these drugs and AAV is confounded by studies that have shown a high prevalence of positive ANCA serologies in patients with tuberculosis (62). Evidence for the association of other medications and AAV is limited to isolated case reports (63)(64)(65).…”
Section: Drugs Associated With Aavmentioning
confidence: 99%
“…Both isoniazid and rifampin have been implicated as causes of vasculitis in case reports (60,61), but the association between these drugs and AAV is confounded by studies that have shown a high prevalence of positive ANCA serologies in patients with tuberculosis (62). Evidence for the association of other medications and AAV is limited to isolated case reports (63)(64)(65).…”
Section: Drugs Associated With Aavmentioning
confidence: 99%
“…It usually occurs within 1–3 weeks after a drug is started. It has been reported in association with antithyroid drugs such as propylthiouracil, methimazole, carbimazole and other drugs including penicillamine,7 hydralazine, minocycline, rifampin, phenytoin, cefotaxime,8 indomethacin9 and clozapine. It is usually associated with high titres of ANCA antibodies with MPO specificity 10.…”
Section: Discussionmentioning
confidence: 99%
“…Urticaria, maculopapular and erythematous rash are more common reactions than other immediate reactions such as anaphylaxis and bronchospasm [1,2,11,12]. Although some anecdotal cases of vasculitis have been reported related with cephotaxim, cefuroxim and cefprozil, cefoperazone has not been reported to cause vasculitic complications before [13-15]. …”
Section: Case Presentationmentioning
confidence: 99%